The effect of soil resistivity on the LV surge environment - Yang, Shuxin (My University, 2007)
Due to the high soil resistivities and high frequency of lightning strikes in South Africa, the background theory about the effect of soil resistivity on the LV surge environment is important, but the present local and international standards do not give reasonable explanations for this effect. The previously published experimental results and research results related to this effect were investigated. From these investigations, it can be shown that the soil resistivity can affect surge generation, surge propagation and surge attenuation significantly. Also, soil resistivity plays a main role in the lightning surges caused by both direct strikes and indirect strikes, which can cause severe damage to the LV distribution system. Soil resistivity also has a significant impact on the resistance of an earth electrode.
Student Number : 0418388R - MSc(Eng) research report - School of Electrical and Information Engineering - Faculty of Engineering and the Built Environment
Keywords: soil resistivity; lightning strike; surge generation; surge attenuation; surge distribution